2019
DOI: 10.1097/sla.0000000000003370
|View full text |Cite
|
Sign up to set email alerts
|

High Systemic Immune-Inflammation Index is an Adverse Prognostic Factor for Patients With Gastroesophageal Adenocarcinoma

Abstract: Objective: The aim of this study was to determine the clinical role of the systemic immune-inflammation index in patients with resectable adenocarcinoma of the gastroesophageal junction treated with or without neoadjuvant therapy. Background: Adenocarcinoma of the gastroesophageal junction is an aggressive disease, with less than 20% of overall patients surviving more than 5 years after diagnosis, while currently available clinical staging for esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 40 publications
3
95
2
Order By: Relevance
“…Although NLR and BMI have previously been shown to be associated with the prognosis in gastric cancer 12 , 16 , 17 , 25 and many other solid tumors 11 , 19 , 20 , 22 , 26 30 , most studies have investigated them individually and in metastatic patients. In the present study, our results confirmed that similar processes occurred in resectable gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although NLR and BMI have previously been shown to be associated with the prognosis in gastric cancer 12 , 16 , 17 , 25 and many other solid tumors 11 , 19 , 20 , 22 , 26 30 , most studies have investigated them individually and in metastatic patients. In the present study, our results confirmed that similar processes occurred in resectable gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the suppression perioperative anti-tumor immune function could facilitate the formation of new metastases and promote postoperative metastasis and recurrence [34,35]. Numerous studies have also shown that some markers of hematological components, such as the NLR, LMR and SII, can comprehensively indicate the balance of the host immune system and have been considered prognosis-related indicators in malignancies [36][37][38]. An increased NLR or SII and a decreased LMR are associated with an adverse prognosis in ovarian cancer [13][14][15].…”
Section: Tablementioning
confidence: 99%
“…When combining these three parameters, a systemic immune-inflammation score (SII) has emerged, calculated by using a formula (SII = NE×LY/PLT), first described in 2014 to explore its prognostic value in hepatocellular carcinoma [39]. Jomrich et al also introduced it for EJA and found that a higher SII contributes to poor OS and DFS in EJA patients who underwent esophagectomy with or without receiving neoadjuvant treatment [40].…”
Section: Hematologic Parametersmentioning
confidence: 99%